2023
DOI: 10.3390/ijms24021116
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Histopathologic and Genetic Features of Rhabdoid Meningiomas

Abstract: Rhabdoid meningiomas (RM) shows heterogeneous histological findings, and a wide variety of chromosomal copy number alterations (CNA) are associated with an unpredictable course of the disease. In this study, we analyzed a series of 305 RM samples from patients previously reported in the literature and 33 samples from 23 patients studied in our laboratory. Monosomy 22-involving the minimal but most common recurrent region loss of the 22q11.23 chromosomal region was the most observed chromosomal alteration, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“… 30 However, later work suggested that the association between rhabdoid histology and poor clinical outcomes applied primarily to a small subset of rhabdoid cases, leading to the removal of this criterion from the WHO 2021 updated classification scheme. 31 Efforts to identify genetic features defining the subset of clinically aggressive rhabdoid meningiomas have suggested inactivating BAP1 mutations as an important prognostic marker, with these mutations being present in approximately 10% of tumors exhibiting predominantly rhabdoid morphology and confer significantly worse clinical outcomes, akin to grade 3 meningiomas. 16 Although rhabdoid and papillary morphologic variants do not fulfill WHO CNS5 anaplastic grading criteria in the absence of other high-grade histologic or molecular features, the goal of our study was to explore molecular alterations of meningiomas that predict survival.…”
Section: Discussionmentioning
confidence: 99%
“… 30 However, later work suggested that the association between rhabdoid histology and poor clinical outcomes applied primarily to a small subset of rhabdoid cases, leading to the removal of this criterion from the WHO 2021 updated classification scheme. 31 Efforts to identify genetic features defining the subset of clinically aggressive rhabdoid meningiomas have suggested inactivating BAP1 mutations as an important prognostic marker, with these mutations being present in approximately 10% of tumors exhibiting predominantly rhabdoid morphology and confer significantly worse clinical outcomes, akin to grade 3 meningiomas. 16 Although rhabdoid and papillary morphologic variants do not fulfill WHO CNS5 anaplastic grading criteria in the absence of other high-grade histologic or molecular features, the goal of our study was to explore molecular alterations of meningiomas that predict survival.…”
Section: Discussionmentioning
confidence: 99%
“…RM has been reported to exhibit heterogeneous histological findings and a wide variety of chromosomal alterations, which may contribute to atypical radiological findings like present meningioma. [ 5 ] It is important to recognize that RM may have a variable appearance on neuroimaging and attempt total resection when suspected.…”
Section: Discussionmentioning
confidence: 99%
“…[ 3 ] Rhabdoid meningiomas (RMs) are a rare type of malignant, WHO Grade III, meningioma with an increased tendency for recurrence and possible metastasis and leptomeningeal dissemination. [ 4 , 5 , 9 , 12 , 13 ] The overall prognosis for these patients is commonly poor. [ 16 ] Prominent peritumoral edema, cystic components, and bone involvement have been documented as characteristic neuroimaging findings.…”
Section: Introductionmentioning
confidence: 99%
“…Secretory meningioma KLF4K409Q and TRAF7 mutations 21 Round eosinophil secretions called pseudopsammoma bodies Positive for carcinoembryonic antigens (CEA) and eosinophile periodic acid Shiff (PAS) staining 21 Choroid meningioma Associated with hematological abnormalities and Castleman Syndrome in children 30 Found in supratentorial regions diffusely strong positive with EMA and vimentin rarely focal weak positive with S-100 negative with CK7 31 Rhabdoid meningioma Related to BAP1 mutations 32 Eccentric nuclei, open chromatin, macronucleoli, and eosinophilic perinuclear inclusions, which might be whorled fibrils or compact, waxy spheres 32,33 Transitional (mixed) Common variant typically found in the spinal region and carries both meningothelial and fibrous types, usually with numerous psammoma bodies 29 NF2 mutations 34…”
Section: Nf2 Mutationsmentioning
confidence: 99%
“…Eccentric nuclei, open chromatin, macronucleoli, and eosinophilic perinuclear inclusions, which might be whorled fibrils or compact, waxy spheres 32,33 …”
Section: Introductionmentioning
confidence: 99%